2008
DOI: 10.1038/nmeth.1270
|View full text |Cite
|
Sign up to set email alerts
|

A large genome center's improvements to the Illumina sequencing system

Abstract: The Wellcome Trust Sanger Institute is one of the world's largest genome centers, and a substantial amount of our sequencing is performed with 'next-generation' massively parallel sequencing technologies: in June 2008 the quantity of purity-filtered sequence data generated by our Genome Analyzer (Illumina) platforms reached 1 terabase, and our average weekly Illumina production output is currently 64 gigabases. Here we describe a set of improvements we have made to the standard Illumina protocols to make the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
552
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 640 publications
(559 citation statements)
references
References 11 publications
6
552
0
1
Order By: Relevance
“…Overall, the data suggest similar or better reproducibility than previously reported for microarray-based sequence capture Hodges et al 2007;Okou et al 2007;Bau et al 2009). Importantly, analysis of the uniqueness of obtained read pairs revealed that more than 98% for both runs, were unique, which is higher than previously reported for standard Illumina GAII sequencing without any enrichment method (Quail et al 2008). This clearly shows that no detectable library representation bias has been introduced during the HybSelect process that would compromise the information value of obtained reads.…”
Section: Capture Of Cancer-related Genesmentioning
confidence: 51%
“…Overall, the data suggest similar or better reproducibility than previously reported for microarray-based sequence capture Hodges et al 2007;Okou et al 2007;Bau et al 2009). Importantly, analysis of the uniqueness of obtained read pairs revealed that more than 98% for both runs, were unique, which is higher than previously reported for standard Illumina GAII sequencing without any enrichment method (Quail et al 2008). This clearly shows that no detectable library representation bias has been introduced during the HybSelect process that would compromise the information value of obtained reads.…”
Section: Capture Of Cancer-related Genesmentioning
confidence: 51%
“…The 39 end of these primers is modified with phosphorothioate, preventing degradation of the primer by error-correcting polymerases (Quail et al 2008). The amplified library was flourometrically quantified on a Qubit flourimeter (Invitrogen) and sequenced on an Illumina Genome Analyzer (Princeton Microarray Facility, http://www.genomics.princeton.edu/ microarray/) using the standard Illumina protocols.…”
Section: Production Of the Bar-coded Librarymentioning
confidence: 99%
“…This was postulated by Quail et al (2008) as a means to reduce the inclusion of artifactual chimeric transcripts that are composed of two cDNA fragments into the sequencing library. We also integrated the use of T4 ligase (Enzymatics Inc.) to improve the efficiency of adapter ligation.…”
Section: Discovery Of Non-ets Gene Fusions In Prostate Cancermentioning
confidence: 99%